Self-healing Reed nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
The natural history of Reed nevus in children shows an initial growth phase lasting 6-12 months, followed by an involution phase. Knowing the natural history of the nevus, the dermatologist can monitor it clinically without resorting to surgical removal. The latter will be reserved for esthetically unacceptable cases. Rather than in the differential diagnosis of melanoma, which is very exceptional in the child, dermoscopy is useful together with the clinical features to check that Reed nevus follows its normal involution, highlighting the passage from an initial globular phase to that of pseudopodia, thin striae till to an appearance indistinguishable from a common melanocytic nevus, usually with homogeneous in the center and reticular in the periphery pigmentation. The regression can be sometimes associated with the loss of any melanocytic pattern with more or less evident non-specific residual pigmentation.